2012
DOI: 10.1371/journal.pone.0047477
|View full text |Cite
|
Sign up to set email alerts
|

MSM Enhances GH Signaling via the Jak2/STAT5b Pathway in Osteoblast-Like Cells and Osteoblast Differentiation through the Activation of STAT5b in MSCs

Abstract: Methylsulfonylmethane (MSM) is a naturally occurring sulfur compound with well-known anti-oxidant properties and anti-inflammatory activities. But, its effects on bone are unknown. Growth hormone (GH) is regulator of bone growth and bone metabolism. GH activates several signaling pathways such as the Janus kinase (Jak)/signal transducers and activators of transcription (STAT) pathway, thereby regulating expression of genes including insulin-like growth factor (IGF)-1. GH exerts effects both directly and via IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 50 publications
0
76
0
3
Order By: Relevance
“…MSM has anti-cancer activities such as wound healing and contact inhibition, and can inhibit cell migration through the extracellular matrix in various types of cancers (14,15). Our recent study proved that MSM is able to up-regulate the expression levels of growth hormone receptor (GHR) and signal transducer and activator of transcription 5b (STAT5b) in osteoblast-like cells (16). It is also able to inhibit in vitro ketosis in mouse hepatocytes (17).…”
mentioning
confidence: 99%
“…MSM has anti-cancer activities such as wound healing and contact inhibition, and can inhibit cell migration through the extracellular matrix in various types of cancers (14,15). Our recent study proved that MSM is able to up-regulate the expression levels of growth hormone receptor (GHR) and signal transducer and activator of transcription 5b (STAT5b) in osteoblast-like cells (16). It is also able to inhibit in vitro ketosis in mouse hepatocytes (17).…”
mentioning
confidence: 99%
“…In the studies presented here, we show that in the presence of 200 m M methyl sulfone and when using the Ince culturing system [14] of Primaria plates and WIT-P medium, normal and cancerous human breast cells remained healthy in 3-dimensional structures for at least 3 months in culture, which is a long time to maintain most types of primary cells in culture. Joung et al [31] recently showed that methyl sulfone is nontoxic and in fact induced differentiation of primary bone marrow mesenchymal stem cells. In support of studies by Horvath et al [4] and others [3,5], we did not observe any toxicity of methyl sulfone on human breast cells, whereas normal and cancerous breast tissue cultured in the absence of methyl sulfone acquired characteristics that are associated with sick or unhealthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…Origen y síntesis del metilsulfonilmetano El MSM es una molécula pequeña y de bajo peso molecular (94,13 g/mol) que forma parte en la naturaleza del llamado «ciclo del azufre» 10 . El ciclo del azufre se inicia en las algas y el plancton marino, microorganismos capaces de absorber considerables cantidades de azufre inorgánico procedente del agua de mar y convertirlo en moléculas elementales de azufre orgánico.…”
Section: Factor Oxidativo E Inflamatorio En La Alopecia Androgénica Funclassified
“…Una vez en la atmós-fera, los rayos ultravioleta (UV) del sol lo oxidan a dimetilsulfóxido (DMSO) y, posteriormente, a MSM. Ambos compuestos son muy solubles en agua y se concentran en el vapor atmosférico, retornando de nuevo a la tierra disueltos en la lluvia 10 . Una vez de nuevo en la tierra, el MSM es absorbido por las plantas, los árboles frutales, etc., pasando a formar parte de la alimentación de humanos y animales.…”
Section: Factor Oxidativo E Inflamatorio En La Alopecia Androgénica Funclassified
See 1 more Smart Citation